2017
DOI: 10.1016/j.jsams.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Beta-alanine supplementation enhances judo-related performance in highly-trained athletes

Abstract: In conclusion, 4 weeks of beta-alanine supplementation effectively enhance judo-related performance in highly-trained athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 31 publications
1
88
1
1
Order By: Relevance
“…Chronic β-alanine supplementation is a nutritional strategy that has been used to improve performance in some sports, especially those characterized by high intensity [10, 11, 13]. The ergogenic effect of β-alanine supplementation is related to an increase in carnosine content, which is a dipeptide that has multiple functions [33], mainly muscle buffering [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic β-alanine supplementation is a nutritional strategy that has been used to improve performance in some sports, especially those characterized by high intensity [10, 11, 13]. The ergogenic effect of β-alanine supplementation is related to an increase in carnosine content, which is a dipeptide that has multiple functions [33], mainly muscle buffering [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although the ergogenic effects of β-alanine have been investigated in various exercise models [12], much less is known about its potential use in different sport disciplines. In this regard, studies have examined the β-alanine ergogenic potential mainly in individual sports (i.e., running [11], swimming [10], judo [13] and others). The results, however, are mixed and the performance enhancing effects seem to be related to the specificities of each sport discipline.…”
Section: Introductionmentioning
confidence: 99%
“…Several original and review articles have described the positive effects of long-term beta-alanine supplementation on muscle performance [92][93][94][95][96], and chronic beta-alanine supplementation is a popular ergogenic strategy. It should be noted that a substantial decrease in the HIS content (~30%) in muscles and plasma after beta-alanine supplementation has been reported [89].…”
Section: Effects On Muscle Performance and Fatiguementioning
confidence: 99%
“…Numerous research has since demonstrated that βA supplementation (1.6–6.4 g·day − 1 for ≥28 days) augments the naturally occurring histidine dipeptide, carnosine ( β-alanyl-L-histidine ) within human muscle tissue [25]. As carnosine acts as a physico-chemical buffering agent (with an imidazole ring pK a of 6.83, and relative similarity to intracellular pH (6.5) [68]), βA supplementation was recently reported as producing small, yet significant performance improvements (effect size: 0.210; 95% CI: 0.057, 0.362) across a range of short (60–240 s) duration events [9] including cycling sprint performance [10], judo bouts [11], 800 m sprinting [12] and 1000 m rowing splits [13] in club-level through to well training men.…”
Section: Introductionmentioning
confidence: 99%